Search for W W/W Z resonance production in ℓνqq final states in pp collisions at √s=13 TeV with the ATLAS detector - Onofre, A. (2018)
A search is conducted for new resonances decaying into a W W or W Z boson pair, where one W boson decays leptonically and the other W or Z boson decays hadronically. It is based on proton-proton collision data with an integrated luminosity of 36.1 fb−1 collected with the ATLAS detector at the Large Hadron Collider at a centre-of-mass energy of s√=13 TeV in 2015 and 2016. The search is sensitive to diboson resonance production via vector-boson fusion as well as quark-antiquark annihilation and gluon-gluon fusion mechanisms. No significant excess of events is observed with respect to the Standard Model backgrounds. Several benchmark models are used to interpret the results. Limits on the production cross section are set for a new narrow scalar resonance, a new heavy vector-boson and a spin-2 Kaluza-Klein graviton.